MANAJEMEN LEADERSHIP PADA TK BERBASIS ALAM (Studi Kasus TK Jogja Green School) - Wahyuningsih, Riris (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
This research aims to know the effectiveness of leadership manajement in nature school of Jogja Kindergarten Green School especially for the strategy, the managerial and also the operational in order to determine the result of education quality. The research method uses qualitative approach with case study design, reveal descriptively phenomenon or case in a certain location which promotes naturalness. The result of this research shows that leadership menegement in Jogja Kindergarten Green School gets a positive result. It is proven with the output of the school in which the alumni of this school have abilities that are appropiated with some children development aspects established by goverment. The important thing is the alumni of this school have humanist character that can be used as an important foundation for future succession. Management of this nature school is done in three strategies. The first strategy is in culinary field. Second strategy is in extracurricular field. The third strategy is in enviromental menagement education infrastructure field.